2021
DOI: 10.1111/adj.12873
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators of dental caries among refugee patients attending a public dental service in Victoria

Abstract: Background Little is known about the relationship between dental caries prevalence and the social risk factors of asylum seekers and refugees in Australia. Methods An oral health interview and a clinical oral examination were carried out on 201 asylum seekers and refugees patients, aged 18–68, attending Monash Health Dental Services, Melbourne, Victoria. Results Data illustrated that 82% of participants had at least one tooth with untreated decay. Tooth level analysis revealed that white spot lesions were most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Notably, only a very small proportion of refugees (about 9%) used prophylactic and preventive services. These identified patterns were consistent with previous studies which found a low use of preventive services [ 9 , 30 ], high use of oral surgery and endodontic services [ 12 ], and a high proportion of those seeking emergency dental care [ 3 ] among refugee populations. Refugees tend to use dental services only when in severe pain or when self-treatments do not work [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, only a very small proportion of refugees (about 9%) used prophylactic and preventive services. These identified patterns were consistent with previous studies which found a low use of preventive services [ 9 , 30 ], high use of oral surgery and endodontic services [ 12 ], and a high proportion of those seeking emergency dental care [ 3 ] among refugee populations. Refugees tend to use dental services only when in severe pain or when self-treatments do not work [ 31 ].…”
Section: Discussionsupporting
confidence: 91%